Gonorrhoea and chlamydia in persons with HIV: number needed to screen. (6th April 2019) - Tuddenham, Susan; Ghanem, Khalil G; Gebo, Kelly A; Moore, Richard D; Mathews, William Christopher; Agwu, Allison; Mayer, Kenneth; Schumacher, Christina; Raifman, Julia; Berry, Stephen A
Abstract : Objectives: Current guidelines recommend screening sexually active persons with HIV (PWH) for Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) at least annually. Yet, screening rates in many HIV clinics remain low. In this study, we estimated the number needed to screen (NNS) to detect a NG and/or CT infection at each anatomic site among different subpopulations of PWH. NNS provides a concrete, practical measure to aid in assessing the practical impact of screening. Methods : We included adults in care at three HIV Research Network sites in 2011–2014. Restricting to first tests within each year, annual NNS was defined as number of persons tested divided by number positive. We computed urogenital and extragenital NNS by age and risk group (women, men who have sex with women (MSW) and men who have sex with men (MSM)). Results : A total of 16 864 NG/CT tests were included. Among patients aged ≤25 years, urogenital NNS was similar among women (15 (95% CI 6 to 71)), MSW (21 (95% CI 6 to 167)) and MSM (20 (95% CI 12 to 36)). Over 25, urogenital NNS increased to a greater extent for women (363 (95% CI 167 to 1000)) and MSW (160 (95% CI 100 to 333)) than MSM (46 (95% CI 38 to 56)). The increase for women versus MSM >25 remained significant (p<0.01) in multivariable analysis. Among MSM, rectal NNS was 5 (95% CI 3 to 7) and 10 (95% CI 9 to 12) for ≤25 and for >25 years and pharyngeal NNS values were 8 (95% CI 5 to 13) and 20 (95% CI 16 to 24). Conclusions: These findings suggest the importance of regular, at least annual NG/CT screening, particularly extragenital, of HIV positive MSM of all ages. They provide some support for age-based cutoffs for women and MSW (eg, universal screening for those aged ≤25 and targeted screening for those aged >25 years).